PENGARUH PERSEPSI PEMAHAMAN WAJIB PAJAK, MANFAAT, KEMUDAHAN PENGGUNAAN, DAN KEPUASAN WAJIB PAJAK TERHADAP PENGGUNAAN SISTEM E-FILING - Annastasia Lizkayundari; Febrian Kwarto (BALANCE: Jurnal Akuntansi, Auditing dan Keuangan, 2018)
This study aims to demonstrate empirically the effect of perception understanding taxpayers, usefulness, ease of use and satisfaction of taxpayers to use the e-filing system. This study uses a survey of the taxpayers of employees who are registered in the Tax Office Primary Cengkareng. There are 400 questionnaires distributed, 390 back, and the 385 questionnaires that could be analyzed. The result of this study indicates that the usefulness and satisfaction of taxpayers empirically effect on use e-filing system for individual taxpayers. While perception understanding taxpayers and ease of use have no effect on use e-filing system for individual taxpayers.